Pharmacokinetics, Safety, and Tolerability of Single-Dose Intravenous (ZTI-01) and Oral Fosfomycin in Healthy Volunteers - Wenzler, E.; Ellis-Grosse, E. J.; Rodvold, K. A. (Antimicrobial agents and chemotherapy, 2017)
The pharmacokinetics, safety, and tolerability of intravenous (i.v.) fosfomycin disodium (ZTI-01) and oral fosfomycin tromethamine were evaluated after a single dose in 28 healthy adult subjects. Subjects received a single 1-h i.v. infusion of 1 g and 8 g fosfomycin disodium and a single dose of 3 g oral fosfomycin tromethamine in a phase I, randomized, open-label, three-period crossover study. Serial blood and urine samples were collected before and up to 48 h after dosing. The mean pharmacokinetic parameters ± standard deviations of fosfomycin in plasma after 1 g and 8 g i.v., respectively, were the following: maximum clearance of drug in serum ( C max ), 44.3 ± 7.6 and 370 ± 61.9 μg/ml; time to maximum concentration of drug in serum ( T max ), 1.1 ± 0.05 and 1.08 ± 0.01 h; volume of distribution ( V ), 29.7 ± 5.7 and 31.5 ± 10.4 liters; clearance (CL), 8.7 ± 1.7 and 7.8 ± 1.4 liters/h; renal clearance (CL R ), 6.6 ± 1.9 and 6.3 ± 1.6 liters/h; area under the concentration-time curve from 0 to infinity (AUC 0–∞ ), 120 ± 28.5 and 1,060 ± 192 μg·h/ml; and half-life ( t 1/2 ), 2.4 ± 0.4 and 2.8 ± 0.6 h. After oral administration, the parameters were the following: C max , 26.8 ± 6.4 μg/ml; T max , 2.25 ± 0.4 h; V /F, 204 ± 70.7 liters; CL/F, 17 ± 4.7 liters/h; CL R , 6.5 ± 1.8 liters/h; AUC 0–∞ , 191 ± 57.6 μg · h/ml; and t 1/2 , 9.04 ± 4.5 h. The percent relative bioavailability of orally administered fosfomycin was 52.8% in relation to the 1-g i.v. dose. Approximately 74% and 80% of the 1-g and 8-g i.v. doses were excreted unchanged in the urine by 48 h compared to 37% after oral administration, with the majority of this excretion occurring by 12 h regardless of dosage form. No new safety concerns were identified during this study. The results of this study support further investigation of i.v. fosfomycin in the target patient population, including patients with complicated urinary tract infections and pyelonephritis.